The Application of Learning Model SQ4R (Survey, Question, Read, Reflect, Recite, Review) can Increase Activeness and Learning Outcomes of Student - Olivia Frances Rivan; Suharto -; Neny Chuinda (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
The objective of this study is to analyze implementation of SQ4R learning method, students ' active participation and students ' achievement in the subject